NÍVEL DE CONHECIMENTO E PRATICA DE HIDRATAÇÃO EM PRATICANTES DE ATIVIDADE FÍSICA EM ACADEMIA - Lumena Carneiro Graciano; Fabrícia Geralda Ferreira; Silvia Maria Saraiva Valente Chiapeta; Lyvia Barros Scolforo; Wellington Segheto (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
This study aimed to verify the level of knowledge and hydration habits of physical activity practitioners. We evaluated 185 subjects (25,2 ± 5,9 years) with a questionnaire containing objective questions on the sport practiced, knowledge and habits of hydration during exercise. We used descriptive statistics and the results are presented using percentage distribution. The most practiced was the weight (71.3%), with time practice over 18 months (40.5%). That most of the evaluated hydrates (72.4%), regardless of the season (61.0%), worry about the liquid ingested (63.7%), consume water as liquid replenishes (56.5%), worry about the type of clothing and fabric ( 69.1%), do not weigh before and after exercise (45.4%) and prefer to consume cold liquids (72.4%). Regarding knowledge about hydration, most indicated that hydration must occur before the sensation of thirst (74.0%), Gatorade was the best known electrolyte replenishes (55.9%) and consumed (69.1%), and the orange flavor the most used (35.2%). Most do not know how to hydrate (48.6%) and do not know the function of isotonic (40.0%), and had not received guidance on the correct form of hydration (60.0%). Despite having a level of knowledge about hydration, this is still incipient. It is necessary to expand the number of individuals using the weighing technique, as well as the students' knowledge about the function of an isotonic and the best strategies of fluid replacement during activity.